Placing knowledge equity at the heart of the UN Ocean Decade: an Early Career Researcher perspective - West, Lindsey; Contreras Liedtke, Niza; Kamara, Martha Kadijatu; Pozo Buil, Mercedes; Das, Jewel; Gallegos, Cristóbal (Frontiers in Ocean Sustainability, 2025)
The UN Ocean Decade provides a framework for stakeholders and rights-holders to come together to develop transformative ocean solutions for sustainable development. We are a group of Early Career Researchers (ECR) from diverse backgrounds with a shared commitment to working toward the Ocean Decade outcomes. Our article offers an ECR perspective on the fundamental importance of knowledge equity for achieving the Ocean Decade's vision of “the science we need for the ocean we want.” Knowledge equity is imperative for confronting the “business as usual” approach to ocean sustainability as it requires us to confront and dismantle extractive practices of knowledge production. We reflect on how the dominance of western science in research and policy and the systematic marginalization of diverse knowledge systems has led to inequitable outcomes for ocean-dependent people. Using real-world examples, we demonstrate the progress we can make toward ocean sustainability when we place knowledge equity at the heart of our work. We conclude with a call to action to ensure that knowledge equity is embedded as both a principle and a practice within the Ocean Decade framework. We invite all ocean professionals to join us in: (1) adopting an intentional practice of reflexivity in our work; (2) confronting colonial ways of thinking, knowing, and doing; and (3) dismantling knowledge hierarchies that permeate ocean science and practice. By implementing these actions, we can create meaningful and inclusive spaces for collaboration and become a more respectful and effective global ocean community.